1998
DOI: 10.1086/301927
|View full text |Cite
|
Sign up to set email alerts
|

Fine Localization of the Nijmegen Breakage Syndrome Gene to 8q21: Evidence for a Common Founder Haplotype

Abstract: Nijmegen breakage syndrome (NBS) is a rare autosomal recessive disorder characterized by microcephaly, a birdlike face, growth retardation, immunodeficiency, lack of secondary sex characteristics in females, and increased incidence of lymphoid cancers. NBS cells display a phenotype similar to that of cells from ataxia-telangiectasia patients, including chromosomal instability, radiation sensitivity, and aberrant cell-cycle-checkpoint control following exposure to ionizing radiation. A recent study reported gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 18 publications
2
21
2
Order By: Relevance
“…The overlapping cellular abnormalities between AT and NBS prompted us to determine the impact of Nbs1 deficiency on Chk2 regulation. The NBS-derived LCL 1548 and GM07078A, homozygous for truncation mutations of the NBS1 gene (835de14 and 657de15, respectively) (7,47,49) were, unlike normal and AT cells, negative for Nbs1 protein ( Fig. 2A).…”
Section: Atm-dependent Chk2 Phosphorylation In Normal Cell Linesmentioning
confidence: 99%
“…The overlapping cellular abnormalities between AT and NBS prompted us to determine the impact of Nbs1 deficiency on Chk2 regulation. The NBS-derived LCL 1548 and GM07078A, homozygous for truncation mutations of the NBS1 gene (835de14 and 657de15, respectively) (7,47,49) were, unlike normal and AT cells, negative for Nbs1 protein ( Fig. 2A).…”
Section: Atm-dependent Chk2 Phosphorylation In Normal Cell Linesmentioning
confidence: 99%
“…The NBS1 gene was mapped to 8q21-24 by functional complementation assays using microcellmediated chromosome transfer (Komatsu et al, 1996;Matsuura et al, 1997). The gene was independently mapped to a 1.1-cM interval surrounding marker D8S1811 (Saar et al, 1997;Cerosaletty et al, 1998) and from this candidate region the NBS1 gene was identified (Matsuura et al, 1998a;Carney et al, 1998;Varon et al, 1998). A protein-truncating 5-bp NBS1 deletion, 657del5, has been found in most NBS families (more than 80%) with Slavic origins, demonstrating the presence of a common founder effect.…”
Section: Introductionmentioning
confidence: 99%
“…The NBS1 gene is located on human chromosome 8q21 (6,20,22,26) and encodes a ubiquitously expressed protein of 754 amino acids (aa) termed nibrin or p95. All known NBS1 mutations are clustered between nucleotides 657 and 1142 of the gene, and all are predicted to truncate the nibrin protein.…”
mentioning
confidence: 99%